(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The emergence of resistant strains of bacteria has seriously limited our ability to treat bacterial illness, and new antibiotics are desperately needed. In this study, the plant extracts were prepared by using diff. solvents (Acetone, EtOH and MeOH). Antimicrobial activity of plant extracts, Antibiotics (Amoxicillin, Ceftazidime, Ciprofloxacin, Amphotericin-B and Fluconazole) and combinations has been done by Agar well Diffusion method. The results of this study showed that ethanol and methanol extract show higher activity against selected pathogenic species. HPTLC has been also performed to check if there any new compound formed or not by combination of extract and antibiotics. The findings of this study suggest that combining plant extract with antibiotics may be effective in battling newly developed drug-resistant microbes